Multivariate analysis and chemometric characterisation of textile wastewater streams - Jerič, Tina (Acta chimica slovenica, 2013)
The aim of this work was to design a quick and reliable method for the evaluation and classification of wastewater streams into treatable and non-treatable effluents for reuse/recycling. Different chemometric methods were used for this purpose handling the enormous amount of data, and additionally to find any hidden information, which would increase our knowledge and improve the classification. The data obtained from the processes description, together with the analytical results of measured parameters' characterising the wastewater of a particular process, enabled us to build a fast-decision model for separating different textile wastewater outlets. Altogether 49 wastewater samples from the textile finishing company were analysed, and 19 different physical chemical measurements were performed for each of them. The resulting classification model was aimed at an automated decision about the choice of treatment technologies or a prediction about the reusability of wastewaters within any textile finishing or other company having similar characteristics of wastewater streams.
Keywords: chemomterics; čiščenje odpadnih voda; finishing wastewater; kemometrijske metode; multivariate data analysis; odpadne vode; tekstilna industrija; wastewater treatment